First-principles DFT and BoltzTraP investigation of multifunctional properties of XNiH3 (X = Li, Na, K) perovskite hydrides: Thermoelectric and hydrogen storage potential - Ayoub Koufi; Younes Ziat; Hamza Belkhanchi (Next Energy)
This work presents a comprehensive first-principles investigation of the structural, electronic, thermoelectric, and hydrogen storage properties of XNiH3 (X = Li, Na, K) perovskite-type hydrides, using density functional theory (DFT) within the generalized gradient approximation (GGA), coupled with the WIEN2k and BoltzTraP codes. The novelty of this study lies in the dual exploration of the thermoelectric and hydrogen storage functionalities of these unexplored materials, which have not yet been synthesized experimentally. Structural optimization confirms stable cubic perovskite configurations (Pm-3m), with lattice parameters increasing from Li to K. Electronic band structure and density of states analyses reveal metallic behavior across all compounds, which is favorable for both charge transport and hydrogen desorption kinetics. Thermoelectric calculations in the 300–900 K range show n-type conduction with negative Seebeck coefficients, and a maximum ZT of 0.09 for LiNiH3 at 800 K, outperforming several known oxide and halide perovskites. Additionally, the calculated gravimetric hydrogen storage capacities are 4.37% (LiNiH3), 3.54% (NaNiH3), and 2.98% (KNiH3), confirming the lightweight character and storage potential of these hydrides. These results highlight the multifunctional potential of XNiH3 compounds for integrated energy applications, particularly in systems combining waste heat recovery and reversible hydrogen storage. Theoretical insights provided here can serve as a foundation for future experimental validation and material design.